Uji Hedonik Kerupuk yang Disubtitusi oleh Lumatan Kulit Ikan Tuna (Thunnus sp.) dan Kulit Ikan Kambing-Kambing (Abalistes stellaris): Variasi Persentase Subtitusi - Aulia Putri; Lia Handayani; Indria Mahgfirah (Jurnal TILAPIA, 2024)
Some fish crackers on the market contain carbohydrates and have a high ability to absorb oil. To add nutrition to crackers by adding fish skin mash sturgeon. The purpose of this study was to determine the effect of the addition of fish skin with the same concentration and the substitution of tapioca flour with different amounts on the sensory value (hedonic test) of 30 semi-trained panelists. This study was conducted using experimental laboratory methods, with 2 (two) factors, namely the type of fish skin: tuna skin (thunnus sp) and goat fish skin (abalistes stellaris). Factors for the comparison of fish skin mash: 10%, 20%, 30%, 60% and the comparison of tapioca flour, 70%, 60%, 50%, 20%. The panelists still liked the results of the cracker hedonic test in all treatments, but treatment I (control) had characteristics such as a taste score of 7.33 ± 1.124, aroma 7.37 ± 1.066, texture 7.20 ± 0.887 (brittle and slightly felt like fish skin), and color 7.47±1.106 (generally yellow-white like crackers). The use of mashed fish skin can affect the hedonic value of fish cracker.